Photon vs. proton radiochemotherapy: effects on brain tissue volume and perfusion - Petr, Jan; Beuthien-Baumann, Bettina (Radiotherapy and oncology, 2018)
Background and purpose - To compare the structural and hemodynamic changes of healthy brain tissue in the cerebral hemisphere contralateral to the tumor following photon and proton radiochemotherapy. - Materials and methods - Sixty-seven patients (54.9±14.0years) diagnosed with glioblastoma undergoing adjuvant photon (n=47) or proton (n=19) radiochemotherapy with temozolomide after tumor resection underwent T1-weighted and arterial spin labeling MRI. Changes in volume and perfusion before and 3 to 6months after were compared between therapies. - Results - A decrease in gray matter (GM) (−2.2%, P<0.001) and white matter (WM) (−1.2%, P<0.001) volume was observed in photon-therapy patients compared to the pre-radiotherapy baseline. In contrast, for the proton-therapy group, no significant differences in GM (0.3%, P=0.64) or WM (−0.4%, P=0.58) volume were observed. GM volume decreased with 0.9% per 10Gy dose increase (P<0.001) and differed between the radiation modalities (P<0.001). Perfusion decreased in photon-therapy patients (−10.1%, P=0.002), whereas the decrease in proton-therapy patients, while comparable in magnitude, did not reach statistical significance (−9.1%, P=0.12). There was no correlation between perfusion decrease and either dose (P=0.64) or radiation modality (P=0.94). - Conclusions - Our results show that the tissue volume decrease depends on radiation dose delivered to the healthy hemisphere and differs between treatment modalities. In contrast, the decrease in perfusion was comparable for both irradiation modalities. We conclude that proton therapy may reduce brain-volume loss when compared to photon therapy.